The Power of Brands and its influence on Consumer Behaviour - A study from the Indian Perspective - Bhati, Roopangi (2013)
The main aim of this paper is to study and assess whether brands influence the decisions and the choices consumers make when selecting a product or service. Branding and consumer behaviour are gradually becoming the epitome of all marketing environments due to the value consumers provide to the brand identity. In the recent decades, the power of marketing has diverted into the hands of consumers. Different elements of brands, the influence branding has on how consumers behave in India and the relationship between the two concepts has been studied in this paper. Furthermore, this paper also emphasises about the consumer behaviour, the consumer decision making journey and the needs of consumer. The focus of this dissertation is to explore different academic perspectives, by Indian and International scholars; while also conducting a research to achieve more apt and focused results. The research adopted for this paper is a qualitative methodology, using semi-structured interviews in India and United Kingdom to explore and identify the differences between the consumers of the two nations. The research method, although small in number, identified the key themes that consumers in India focus on when choosing to buy a product or service. A significant relationship between the quality, product and perceived, and brands was noted amongst the interview respondents, as most respondents answers determined that the influence of quality, durability, longevity is high during the consumer decision making. The study collectively answers the research question by showing that consumers are more inclined to a product or service with known quality, regardless of the fact that they would like to be associated with a brand. Brand awareness and visibility also proved to be important to the Indian consumers.